2018
DOI: 10.1016/j.asjsur.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of laparoscopic sleeve gastrectomy from a single center in mainland China

Abstract: LSG is a safe and effective procedure with good five year results. Weight regain remains a concern two years post surgery. Standardization of LSG is important to reduce major complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…To best of our knowledge, the present study is the largest cohort study that evaluated the effectiveness of bariatric surgery among Chinese population using population-based data. [15][16][17][38][39][40] The results of this study were in line with the conclusion of previous observational studies and randomised controlled trials (RCTs), which found that bariatric surgery provided substantial and sustainable effects on weight loss, glycaemic control, and lipid profile improvement. 15,42,[44][45][46] However, observations of the present study were at variance with other studies regarding to diabetes remission and weight loss in quantitative aspect and hypertension remission from qualitative perspective.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…To best of our knowledge, the present study is the largest cohort study that evaluated the effectiveness of bariatric surgery among Chinese population using population-based data. [15][16][17][38][39][40] The results of this study were in line with the conclusion of previous observational studies and randomised controlled trials (RCTs), which found that bariatric surgery provided substantial and sustainable effects on weight loss, glycaemic control, and lipid profile improvement. 15,42,[44][45][46] However, observations of the present study were at variance with other studies regarding to diabetes remission and weight loss in quantitative aspect and hypertension remission from qualitative perspective.…”
Section: Discussionsupporting
confidence: 90%
“…To best of our knowledge, the present study is the largest cohort study that evaluated the effectiveness of bariatric surgery among Chinese population using population‐based data . Also, this study made a comprehensive illustration of metabolic and weight outcomes, including complete and partial remission rates of diabetes, remission rates of hypertension, high LDL‐C, low HDL‐C, high triglycerides and dyslipidaemia, and improvement of BMI, HbA 1c , SBP, DBP, LDL‐C, %TWL, %EWL, and %REWL.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Waist circumference: male >90 cm, female >85 cm. The weight of subjects was stable for at least 3 months prior to surgery [13].…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…Subjects were excluded if they had cardiovascular dis-ease, arthritis, acute inflammatory disease, infectious disease, gastrointestinal surgery previously or were receiving drugs that could alter the lipid profile or the metabolic parameters at inclusion in the study [13].…”
Section: Study Design and Subjectsmentioning
confidence: 99%